Exploring knowledge, attitudes and experience of genitourinary symptoms in women with early breast cancer on adjuvant endocrine therapy. (16th January 2018) - Sousa, M.; Peate, M.; Lewis, C.; Jarvis, S.; Willis, A.; Hickey, M.; Friedlander, M.
Abstract : Clinical trials of adjuvant endocrine therapy in women with early breast cancer have consistently reported that genitourinary symptoms are common. However, little is known about women's experiences of genitourinary symptoms, their views about the symptoms and how they impact on their lives. The aim of this study was to explore knowledge, attitudes and experiences of genitourinary symptoms among women receiving adjuvant endocrine therapy for early breast cancer. Thirty‐two semi‐structured interviews were conducted and subjected to a rigorous qualitative analysis. Genitourinary symptoms were commonly reported to negatively impact on personal, social and physical activities, were often attributed to anxiety and stress and were a source of embarrassment. Women also commented on the limited information available or provided regarding the potential genitourinary adverse effects of adjuvant endocrine therapy. There was a general lack of awareness that their symptoms could be associated with or exacerbated by adjuvant endocrine therapy. Women indicated a preference to receive information and advice about potential management options from either their general practitioner or specialist. These findings underscore the importance of improving communication and increasing awareness among both clinicians and patients about the potential impact of adjuvant endocrine therapy on genitourinary symptoms.